Resident evaluation of community development programmes by local government / Thenmolli Vadeveloo - Thenmolli, Vadeveloo (2017)
Community Development Programmes (CDPs) of the local authorities (LAs) exemplify a new and significant approach to nurture better environment in response to the needs and problems raised by the people. However, many of the initiatives are not in tandem with the requirements of the people as local governments tend to merely adopt existing policy instruments without undertaking an in-depth evaluation on their effectiveness to the current application. This study aims at identifying the perception of the local people on CDPs and the effectiveness of such programmes by the LAs. The research framework in this study adopts social capital theory and service quality method for the development of theoretical understanding on community development. This study adopts a quantitative method using a simple random sampling of seven LAs in Negeri Sembilan, i.e. two Municipal and five District Councils. Data were gathered through the survey method from 369 participants residing under these LAs. Data collected were analysed using factor analysis, descriptive statistics, t-test, ANOVA and Importance Performance Analysis (IPA). The hypotheses were tested using Multiple Regression Analysis. The findings of the research indicate a significant difference between the total expectations and actual level of delivery of community development services. The study revealed that the CDPs would have a greater impact if the local communities are more engaged, thus assisting in accomplishing the objectives of local government. Strategies suggested include planning and implementation of development programmes, promoting CDPs, policy formulation, adequate exploration on CDPs and the performance of the LAs towards achieving the objectives. Thus, this study provides pragmatic and theoretical implications for the academic advancement in the field and enhances the modality of implementation for practitioners.